FROM MEDIATION TO ADVOCACY: POST-DIVORCE WOMEN’S EMPOWERMENT THROUGH RELIGIOUS COURT PRACTICES IN SOUTH SULAWESI, INDONESIA - Saidah; Badruzzaman; Nur Afiah; Luthfiah. M; Nur Awaliyah (Institut Agama Islam Negeri Bone, 2026)
This study investigates the transformation of court-based mediation from a dispute resolution mechanism into an advocacy-oriented legal strategy for women’s empowerment after divorce in South Sulawesi, Indonesia. Using a qualitative field research design, the study examines how mediators within the Religious Court system facilitate women’s access to post-divorce rights, address power imbalances during mediation, and link legal procedures with psychosocial and economic support networks. Data were generated through in-depth interviews, participant observation, and document analysis involving mediators, divorced women, judges, legal practitioners, government officials, and civil society organizations. The findings demonstrate that mediators increasingly operate as legal-humanist advocates who translate complex legal norms into accessible knowledge, create safer and more equitable negotiation spaces, and mitigate structural vulnerabilities stemming from low legal literacy, economic dependency, and persistent social stigma. Three key contributions of court-based mediation are identified: legal empowerment through rights clarification, gender-sensitive mediation that rebalances unequal power relations, and cross-sector referrals that enhance women’s resilience and post-divorce autonomy. Nevertheless, the effectiveness of these practices remains limited by systemic constraints, including fragmented institutional authority, procedural rigidity, and weak post-judgment enforcement, which often produce legal alienation and undermine women’s advocacy capacity. The study argues that sustainable post-divorce empowerment requires the institutionalization of integrated advocacy models within the court system and concludes by highlighting the importance of cross-sector collaboration through a “closing the loop” framework connecting mediators, legal aid institutions, and women’s protection agencies, alongside reforms in mediator training to incorporate post-judgment advocacy as a core competency.